2019
DOI: 10.1121/1.5111345
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydrostatic pressure on phase-change contrast agent activation by pulsed ultrasound

Abstract: A phase-change contrast agent (PCCA) can be activated from a liquid (nanodroplet) state using pulsed ultrasound (US) energy to form a larger highly echogenic microbubble (MB). PCCA activation is dependent on the ambient pressure of the surrounding media, so any increase in hydrostatic pressure demands higher US energies to phase transition. In this paper, the authors explore this basic relationship as a potential direction for noninvasive pressure measurement and foundation of a unique technology the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Experimentally, it has been found that a prominent peak negative pressure (PNP) nucleation threshold exists, above which the nucleation probability increases with the acoustic pressure amplitude and that this threshold, counterintuitively, lowers with an increase in ultrasound frequency and with a decrease in ambient pressure [9,12,[21][22][23][24][25][26][27][28][29][30]. These observations are in line with what is predicted from both classical nucleation theory [31] and superharmonic focusing [23,32], and by the combination of the two [33,34]. Superharmonic focusing results from the focusing of higher harmonics with wavelengths on the order of the droplet diameter that are generated through nonlinear propagation of the transmitted ultrasound wave [32].…”
supporting
confidence: 69%
“…Experimentally, it has been found that a prominent peak negative pressure (PNP) nucleation threshold exists, above which the nucleation probability increases with the acoustic pressure amplitude and that this threshold, counterintuitively, lowers with an increase in ultrasound frequency and with a decrease in ambient pressure [9,12,[21][22][23][24][25][26][27][28][29][30]. These observations are in line with what is predicted from both classical nucleation theory [31] and superharmonic focusing [23,32], and by the combination of the two [33,34]. Superharmonic focusing results from the focusing of higher harmonics with wavelengths on the order of the droplet diameter that are generated through nonlinear propagation of the transmitted ultrasound wave [32].…”
supporting
confidence: 69%
“…Experimentally, it has been found that a prominent peak negative pressure (PNP) nucleation threshold exists above which the nucleation probability increases with the acoustic pressure amplitude and that this threshold, counterintuitively, lowers with an increase in ultrasound frequency and with a decrease in ambient pressure [9,12,[21][22][23][24][25][26][27][28][29][30]. These observations are in line with what is predicted from both classical nucleation theory [31] and superhamonic focusing [23,32], and by the combination of the two [33,34]. Superharmonic focusing results from the focusing of higher harmonics with wavelengths on the order of the droplet diameter that are generated through nonlinear propagation of the transmitted ultrasound wave [32].…”
supporting
confidence: 69%
“…This MPa is well below reported thresholds of 13.7 to 21 MPa for 1.1-MHz ultrasound cavitation in tissue [42], but the mechanical index is above the accepted diagnostic ultrasound imaging threshold of 1.9 [59]. While the cavitation threshold depends on experimental variables such as dissolved gas content, nucleation sites, and water concentration [22], [26], [41], [53], [60], we found the energy levels required for HnD vaporization to be lower than those of cavitation in blank phantoms or OBnD phantoms with nanodroplet nucleation sites. It is important to note this threshold is also dependent on the imaging environment.…”
Section: Discussionmentioning
confidence: 59%